Psychiatric Symptoms in Patients with Immune-Related Mucocutaneous Lichen Planus - Narges Hejazi; Hossein Eslami; Ali Reza Shafiee-Kandjani; MohamadReza Ranjkesh; Behzad Shalchi; Fatemeh Eskandarpour (ImmunoAnalysis)
Background: Lichen planus (LP) is one of the most common chronic mucocutaneous diseases with an underlying immunological component. Although the pathogenesis of this condition is not exactly known, numerous studies have been conducted due to the significance of this disease and its high prevalence. Several risk factors and various contexts have been identified for this condition; however, the primary cause is still not fully understood. Some genetic and environmental factors may be involved in the development of the disease. The present study was conducted to examine psychiatric symptoms in patients with cutaneous-oral LP (COLP) referred to the dermatology clinic of Sina Hospital of Tabriz city, northwest of Iran. Methods: This descriptive study was conducted on 31 patients with LP and 31 healthy individuals referred to the dermatology clinic of Sina Hospital in Tabriz. The information required was collected using the SCL-90-R standard questionnaire, and the data were analyzed using descriptive and inferential statistics with the help of SPSS v.23 and multivariate analysis of variance (MANOVA). Results: The results showed that people with COLP do not suffer from serious psychiatric conditions but may have merely mild to moderate psychiatric symptoms. However, the MANOVA test indicated that the symptoms had a significantly higher incidence in patients with oral LP compared to matched control subjects (F (12,47)=13.86, P<0.05). Conclusion: As shown by the SCL-90-R standard checklist, patients with oral LP expressed significantly more psychiatric symptoms than normal individuals, reflecting the need for these patients for more regular assessments.